PENERAPAN MODEL PEMBELAJARAN TWO STAY-TWO STRAY PADA MATERI FUNGSI KELAS VIII DI SMP NEGERI 4 TONDANO - Pilomali, Tiara; Salajang, Santje M.; Pulukadang, Rosiah J. (Dharmas Education Journal (DE_Journal), 2024)
This research is motivated by a lack of mastery of mathematics learning concepts, especially in function material. This is based on the results of observations made by the author showing that students still have difficulty calculating the value of a function and determining the form of presentation of the function and the use of conventional learning methods which make students stiff and bored with mathematics lessons. So to improve students' mastery of concepts and learning outcomes, namely by using the Two Stay-Two Stray learning model. This research method is experimental research conducted on class VIII students at SMP Negeri 4 Tondano. This research design uses a posttest only control design. The population of this study was all students in class VIII, while the research sample consisted of two classes, namely class VIII A, consisting of 32 students, as the experimental class and class VIII B, as the control class, consisting of 32 students. Based on the data, the average learning outcome for the experimental class was 85.94 while the average learning outcome for the control class students was 79.31. The data normality test shows that the data has a normal distribution. The research instrument used was a student learning outcomes test in the form of an essay. The results of data analysis with a significance level of 0.05 obtained tcount > ttable (3.2145 > 1.670). Based on the research results, it can be concluded that the use of the Two Stay-Two Stray learning model in functional material can improve student learning outcomes compared to conventional learning models